Fee-Free Education In Indonesia: A Review Of Fifteen-Years Fee-Free Education Law And The Reality Application And Needs In Bantul District, Yogyakarta - Putri Kramer; Udik Budi Wibowo; Eveline Eveline (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Fee-free education has become crucial to global efforts to achieve the Education for All (EFA) goals. This policy has been implemented in Indonesia through various programs, including the School Operational Assistance (BOS) and Indonesia Smart Program (PIP), to support underprivileged families. However, there still needs to be more funding that parents must cover to support their children's education. This study aims to evaluate the implementation of fee-free education in Bantul District, Yogyakarta, and explore the financial needs that parents still have to meet. The research employs a qualitative method with an exploratory, descriptive approach. Data were collected through interviews with parents, school principals, and teachers in 16 elementary schools in Bantul. The results indicate that the funds provided by the government through BOS and PIP are insufficient to cover the full education costs, particularly for students with special needs. Parents still face additional fees, such as uniforms, books, and transportation. In conclusion, while the fee-free education policy is in place, increased funding allocation is necessary to ensure that all children, especially those from disadvantaged families, can access quality education without financial burdens.